SANKSI TINDAK PIDANA KEKERASAN SECARA FISIK DI LINGKUP RUMAH TANGGA YANG TIDAK MENGHALANGI PEKERJAAN (STUDI PENGADILAN NEGERI PALEMBANG NOMOR 100/PID.SUS/2021/PN PLG): Sanctions for Criminal Actions of Physical Violence in the Household Wich Do Not Blow Work (Study of Palembang State Court Number 100/Pid.Sus/2021/Pn Plg - I Gusti Agung Faradilla; Ermania Widjajanti (Universitas Trisakti, 2024)
Physical violence is an act that causes in pain, falling sick or serious injury committed within the household between husband and wife and vice versa. A criminal sanction is a causal punishment for someone committing a crime that will receive criminal sanctions or other punishment from the authorities. Case Number 100/Pid.Sus/2021/PN. PLG contained acts of domestic violence that did not hinder work, in which the defendant physically assaulted the victim-witness who had caught the defendant checking-in with another woman which resulted in bruises on his hands and abdominal and pelvic cramps, in the imposition of articles and the sanctions imposed were inappropriate . In this case, the creation of a thesis using a research method which contains the object of research in the form of sanctions for domestic violence crimes that do not hinder work. The type used is the normative type, with analytical descriptive characteristics, with secondary data and data analysis using qualitative analysis methods. The conclusions drawn from this study are that the indictment given to the defendant is not appropriate based on Article 44 paragraph (1) of Law Number 23 of 2004. The sanction given to the defendant for 6 (six) months is not appropriate based on the purposes of 3R and 1D punishment, and the defendant should have been given an additional 3 (three) years of probation so that the defendant would feel deterrent.